Nephrocalcinosis - latest reports on risk factors - Tomasz Dudzik; Łucja Dudzik; Igor Domański; Aleksandra Kozieł; Paulina Wójcik; Natalia Kuderska (Termedia Publishing House, 2024)
This review synthesises recent discoveries in the risk factors of nephrocalcinosis, with a particular focus on novel findings. Nephrocalcinosis, characterised by the deposition of calcium salts in the renal parenchyma, is linked to a variety of genetic, metabolic, dietetic, and environmental contributors. The study emphasises the critical role of advanced imaging techniques in diagnosis and the identification of new genetic mutations in genes such as CLCN5, CASR , and SLC34A3 as significant contributors to the condition. The paper highlights the importance of recognising these novel risk factors for better diagnosis, treatment, and prevention of nephrocalcinosis. It calls for further research to explore these new dimensions, particularly the genetic underpinnings and environmental exposures, to develop more effective management strategies and potentially prevent the onset of this complex renal condition.